A Narrative Inquiry into the Experiences of Two Non-Aboriginal Counsellors Working with Aboriginal People - Bowden, Amanda; Caine, Vera; Yohani, Sophie (Canadian Journal of Counselling and Psychotherapy, 2017)
In this narrative inquiry we explored the experiences of two non-Aboriginal counsellors who worked with Aboriginal clients in Canada. Narrative inquiry is a relational methodology that allows researchers to attend to experience over time, place, and social contexts. With a call to develop a better understanding of the health issues facing Aboriginal peoples, counsellors need to have a strong understanding of the changing social conditions and focus beyond existing care paradigms. In order to provide culturally relevant care, non-Aboriginal counsellors need to engage in advocacy, outreach, community-based interventions, and consultations with indigenous practitioners. We highlight the need for both culture-informed and social justice perspectives to place counselling practice with Aboriginal peoples in the context of culture, history, and sociopolitical realities.